Cyclic oxidation and rumpling behaviour of single phase β-(Ni, Pt)Al coatings with different thickness of initial Pt plating. (October 2016) - Yang, Y.F.; Jiang, C.Y.; Yao, H.R.; Bao, Z.B.; Zhu, S.L.; Wang, F.H.
Graphical abstract: A dual-layered alumina scale consisting of upper equiaxed and inner columnar grains was observed on the β-(Ni, Pt)Al coating specimen with 5 μm Pt after cyclic oxidation at 1100 °C for 200 cycles. The corresponding SAED patterns (b and c) confirm hexagonal crystal structures for the equiaxed and columnar α-Al2 O3 grains, respectively. This unique structure of dual-layer was beneficial for the decreased oxidation rate, and the precipitation of Pt-rich particles along columnar alumina grain boundary may assist to block the outward transportation of Al cations. Highlights: Dual-layered α-Al2 O3 scale was formed on (Ni, Pt)Al coating after oxidation. Pt-rich precipitates were observed in columnar grains of Al2 O3 scale. Higher Pt content in (Ni, Pt)Al coating results in lower Young's modulus and hardness. Besides phase transformation, coating deformability was important to affect rumpling. Al depletion rate was accelerated in turn by severer morphology rumpling. Abstract: Cyclic oxidation behaviour of single phase β-(Ni, Pt)Al coatings with different thickness of initial Pt plating was evaluated at 1100 °C in air. The coating sample of 5 μm Pt showed the best oxidation resistance, and after oxidation a dual-layered structure of alumina scale was formed on this coating with precipitation of Pt-rich particles at both boundary and interior of columnar α-Al2 O3 grains. Comparatively, the coating sample with 8 μm Pt was prone to rumpling due to its lower hardness and Young's modulus, while the severer rumpling behaviour in turn increased the scale spallation tendency and Al depletion rate.